1999
DOI: 10.1016/s0735-1097(99)00366-6
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparison of coronary stent implantation and balloon angioplasty in the treatment of de novo coronary artery lesions (START)

Abstract: Patients who received an intracoronary stent showed a lower rate of restenosis than those treated with conventional balloon angioplasty. The benefit of stenting was maintained four years after implantation, as manifested by a significant reduction in the need for repeat revascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(58 citation statements)
references
References 32 publications
4
51
0
3
Order By: Relevance
“…In early studies, warfarin was used as the standard antithrombotic treatment. 38,47,[51][52][53]56,79,80,82 Ticlopidine has been used more commonly in recent years. In some trials, 57,61 the drug regimen for the stent patients was changed from warfarin to ticlopidine owing to the increased risk of bleeding complications.…”
Section: Adjunctive Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In early studies, warfarin was used as the standard antithrombotic treatment. 38,47,[51][52][53]56,79,80,82 Ticlopidine has been used more commonly in recent years. In some trials, 57,61 the drug regimen for the stent patients was changed from warfarin to ticlopidine owing to the increased risk of bleeding complications.…”
Section: Adjunctive Treatmentmentioning
confidence: 99%
“…However, the comparison of DES and BMS for single-vessel disease does not involve any question of mortality and therefore can easily be represented in a much simpler way. [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69]70+ CIC In this section we introduce a simplified model for this purpose, which can be presented on a single Excel worksheet and encapsulates virtually all the detail of the original LRIG model for comparison of stents.…”
Section: Economic Modelling: Simplified Model For Non-drug Eluting Vementioning
confidence: 99%
“…Coronary arteries larger than 3 mm are considered good candidates for revascularization, and the benefit of coronary stenting has been consistently demonstrated in coronary vessels >3 mm in diameter. [22][23][24] It is well known that restenosis after percutaneous coronary intervention is influenced by vessel diameter and stent occlusion is more frequent in small vessels leading to controversy regarding the utility of stenting in small vessels <3 mm in diameter. 25,26 The issue of small coronary stenting has been addressed in numerous prospective randomized trials of vessels <3 mm in diameter which were analyzed in 2 meta-analyses of the overall results.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19] The need for emergency CABG during the hospitalization was as low as 0.7% in the present study, which might be, at least in part, because of the availability of coronary stents; recent studies have shown the decline of emergency CABG after the introduction of stents and newer adjuvant pharmacological agents. 20 Other factors may also have contributed to this lower rate of emergency CABG in Japan, such as increasing operator volume and hospital experience of PCI.…”
Section: Discussionmentioning
confidence: 99%